2022
DOI: 10.1002/pros.24416
|View full text |Cite
|
Sign up to set email alerts
|

Prostate tumor RON receptor signaling mediates macrophage recruitment to drive androgen deprivation therapy resistance through Gas6‐mediated Axl and RON signaling

Abstract: Background: Androgen deprivation therapy (ADT), or chemical castration, is the first-line therapy for prostate cancer; however, resistance leaves few treatment options. Prostatic tumor-associated macrophages (TAMs) have been shown to promote prostate cancer growth and are abundant in castration-resistant prostate cancer (CRPC), suggesting a role in promoting CRPC. We recently showed a tumor cell-intrinsic mechanism by which RON promotes CRPC. Given previous reports that RON alters prostate cancer cell chemokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…As described previously, RON overexpression in PCa cells enhances CCL2 production for macrophage recruitment and RON-overexpressing tumors alter macrophage state to drive growth under androgen-deprived conditions. It is therefore plausible that combining RON inhibition with macrophage depletion promotes CRPC sensitization to ADT [ 169 ]. Coincidentally, anti CCR2 antagonist could reduce the side effects induced by ADT, although single antibody targeting CCL2 failed in a phase II clinical trial [ 170 ].…”
Section: Promising Strategies For Pca Treatment Via Targeting Tamsmentioning
confidence: 99%
“…As described previously, RON overexpression in PCa cells enhances CCL2 production for macrophage recruitment and RON-overexpressing tumors alter macrophage state to drive growth under androgen-deprived conditions. It is therefore plausible that combining RON inhibition with macrophage depletion promotes CRPC sensitization to ADT [ 169 ]. Coincidentally, anti CCR2 antagonist could reduce the side effects induced by ADT, although single antibody targeting CCL2 failed in a phase II clinical trial [ 170 ].…”
Section: Promising Strategies For Pca Treatment Via Targeting Tamsmentioning
confidence: 99%
“…Prostate tumor-associated macrophages can promote the growth of PCa, and secreted Gas6 can further enhance the activation of RON and AXL receptors in PCa cells, thereby driving CRPC. Targeting RON and macrophages promotes CRPC sensitivity to ADT ( 52 ). Targeting the CSF1 receptor can also reverse macrophage-mediated resistance to androgen blockade in PCa ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…NRP1, serving as a key factor of SARS-CoV-2 virus infection (41), could increase the susceptibility of cancer patients to SARS-CoV-2 virus and targeting (42), and its overexpression is associated with poor prognosis in bladder cancer cells and hepatocellular carcinoma, and inhibiting its expression could promote tumor cell apoptosis (43,44). In addition, the increased expression of SCARB1 could promote cell transformation towards malignancy of clear cell renal cell carcinoma leading to poor prognosis of patients (45), while the over-expression of AXL could accelerate EGFR mutation and promote the metastasis, invasion or drug resistance of tumors such as lung cancer (46), colorectal cancer (47), pancreatic cancer (48) and prostate tumor (49). Then, genetic and epigenetic studies have also shown that high frequencies of SNV, and methylation were noted in these five STGs, which may impact STGs expression in malignancies and affect the prognosis of cancer patients.…”
Section: Discussionmentioning
confidence: 99%